Analysis of the Mechanism for Establishing Trademark Licenses and the Role of Notaries in Ensuring Legal Certainty in Indonesia - Riastya Safira; Siti Malikhatun Badriyah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Trademark registration is very important to guarantee economic rights and exclusive rights for creators, this concerns the legal protection obtained. The problem then is Based on the author's analysis of various sectors of the Law, namely: First, Law Number 2 of 2014 in conjunction with Law Number 30 of 2004 concerning the Position of Notary. Second, Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Third, Law Number 28 of 2014 concerning Copyright. It is clear that there is no Article at all that regulates the formation of a trademark license. The purpose of this study is to analyze: 1) Analyze and determine the mechanism for the formation of intellectual property rights for trademark licenses in the national legal system. 2) analyze and determine the urgency of Notary involvement in the formation of trademark licenses in Indonesia from the perspective of legal certainty. The approach method used in discussing this research problem is the type of normative legal research, using a legislative approach, an analytical approach and a conceptual approach. The data collection method uses literature studies and documentation studies. The results of this study conclude that: 1). The mechanism for establishing intellectual property rights over brand licenses in the national legal system uses the Ministerial Regulation under the Ministry of Law in this case the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 67 of 2016 and HAM Concerning Trademark Registration through the Directorate General of Intellectual Property. Registration is carried out using the bureaucratic mechanism procedures that have been determined by the Ministerial Regulation and technical implementation through bureaucratic instruments at the Directorate General of Intellectual Property of the Ministry of Law and HAM. 2).